UTILIZATION OF RED BEAN (Phaseolus vulgaris L.) AND OYSTER MUSHROOM IN THE MAKING OF ANALOG JERKY - Eveline, Eveline (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2020)
Jerky is a traditional Indonesian processed product which is generally made from real meat. Vegans cannot consume this product, so making vegetable jerky can answer the needs of vegan food consumption variations. The use of red beans as a source of high protein and natural red color like meat, and oyster mushrooms as a source and texture of fiber resembling meat, are considered appropriate in determining the main raw material for making vegetable jerky. This study aims to utilize red beans and oyster mushrooms in the manufacture of vegetable jerky based on the ratio of red bean - oyster mushroom and drying time, and determine the maximum shelf life of vegetable jerky. Initially, red beans and oyster mushrooms are made into a mixture with a ratio (100: 0, 75:25, 50:50, 25:75, and 0: 100) and dried at 50 °C for 6, 7, and 8 hours. The ratio of 75:25 for 8 hours of drying produces vegetable jerky that meets SNI requirements for beef jerky with a protein content of 15.03%; water 4.85%; aw 0.43; hardness 1317 g; hedonic color 5.37, aroma 5.40, taste 4.83, hardness 5.17, and overall 5.47. This ratio is used at a later stage to determine the maximum shelf life (weeks 0, 1, 2, 3, and 4). A series of analyzes refer to the 2nd week as the maximum shelf life with acid number 0.94 mg KOH/g, peroxide number of 2.61 meq/1000g, thiobarbituric acid (TBA) number 0.41 malonaldehyde/kg, fat 5.01%, aw 0.64, water 11.40%, and total plate count (TPC) 4.99 log cfu/g.